Analisis Peran Keluarga Dalam Membentuk Karakter Tanggung Jawab Siswa SD Negeri 5 Ngulak - Ria Anatasia; Muhammad Idris; Mega Prasrihamni (Universitas Muhammadiyah Kuningan, 2025)
This research aims to identify the role of the family in forming responsible character education in grade IV students at SD Negeri 5 Ngulak. The research method used is descriptive qualitative. The population in this study was 24 parents of students at SD Negeri 5 Ngulak. The sample used in this study was 5 parents of students and 1 homeroom teacher from students at SD Negeri 5 Ngulak. Based on research results and discussion about the influence of the family's role in shaping students' responsible character. It was found that the family has an important role in forming and encouraging the formation of students' responsible character at school. The role of the family obtained in this research is as an educator, guide, facilitator and student motivation in guiding the implementation of students' obligations at school. Apart from the role of the teacher, the role of the homeroom teacher is also important in controlling the development of students' responsible character at school by giving assignments and as a reminder if students are not disciplined in carrying out the tasks given. The final finding in this research is that the family has a very important role in forming character. student responsibility both in terms of school discipline and in carrying out assignments.